Senolytic activity of piperlongumine analogues: Synthesis and biological evaluation. Issue 14 (7th August 2018) - Liu, Xingui; Wang, Yingying; Zhang, Xuan; Gao, Zhengya; Zhang, Suping; Shi, Peizhong; Zhang, Xin; Song, Lin; Hendrickson, Howard; Zhou, Daohong; Zheng, Guangrong
Graphical abstract: Abstract: Selective clearance of senescent cells (SCs) has emerged as a potential therapeutic approach for age-related diseases, as well as chemotherapy- and radiotherapy-induced adverse effects. Through a cell-based phenotypic screening approach, we recently identified piperlongumine (PL), a dietary natural product, as a novel senolytic agent, referring to small molecules that can selectively kill SCs over normal or non-senescent cells. In an effort to establish the structure-senolytic activity relationships of PL analogues, we performed a series of structural modifications on the trimethoxyphenyl and the α, β-unsaturated δ-valerolactam rings of PL. We show that modifications on the trimethoxyphenyl ring are well tolerated, while the Michael acceptor on the lactam ring is critical for the senolytic activity. Replacing the endocyclic C2–C3 olefin with an exocyclic methylene at C2 render PL analogues 47 –49 with increased senolytic activity. These α-methylene containing analogues are also more potent than PL in inducing ROS production in WI-38 SCs. Similar to PL, 47 –49 reduce the protein levels of oxidation resistance 1 (OXR1), an important oxidative stress response protein that regulates the expression of a variety of antioxidant enzymes, in cells. This study represents a useful starting point toward the discovery of senolytic agents for therapeutic uses.